2016
DOI: 10.1002/pros.23228
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Metformin and Serum Prostate‐Specific Antigen Levels

Abstract: BACKGROUNDMetformin is the first‐line oral antihyperglycemic of choice for individuals with type 2 diabetes. Recent evidence supports a role for metformin in prostate cancer chemoprotection. However, whether metformin indeed influences prostate biology is unknown. We aimed to study the association between metformin and serum prostate‐specific antigen (PSA) levels—the primary prostate cancer biomarker.METHODSWe conducted a cross‐sectional study of 326 prostate cancer‐free men with type 2 diabetes were recruited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…Moreover, patients on drugs that may affect PSA levels, namely 5α-reductase inhibitors or nonsteroidal or anti-inflammatory drugs were not excluded from analysis. Jayalath et al [ 9 ] reported a relationship between metformin use and serum PSA levels in which mean PSA levels were 30% lower in metformin users, similar to our observation. In addition, an inverse dose–response relationship was observed.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Moreover, patients on drugs that may affect PSA levels, namely 5α-reductase inhibitors or nonsteroidal or anti-inflammatory drugs were not excluded from analysis. Jayalath et al [ 9 ] reported a relationship between metformin use and serum PSA levels in which mean PSA levels were 30% lower in metformin users, similar to our observation. In addition, an inverse dose–response relationship was observed.…”
Section: Discussionsupporting
confidence: 90%
“…Several studies have reported a negative association between PCa and serum PSA, the most widely used biomarker for PCa risk and progression. [ 9 ] However, it is still not clear whether diabetes exerts a protective role against PCa or whether long-term use of metformin itself is related to decreased PSA levels.…”
Section: Introductionmentioning
confidence: 99%
“…Our findings validate the importance of several wellknown co-morbid conditions such as coronary artery atherosclerosis [19,20], chronic obstructive pulmonary disease [19,[21][22][23], congestive heart failure [19,[23][24][25], anaemia [19,26] and diabetes mellitus [23,25,[27][28][29][30] in terms of their ability to predict perioperative complications. These conditions, which are directly or indirectly related to cardiovascular co-morbidities, are generally common in PCa patients [31].…”
Section: Discussionmentioning
confidence: 49%
“…A recent meta-analysis, which included 30 cohort studies ( n = 1,660,795), demonstrated that metformin improved both overall survival (HR 0.72, 95% CI 0.59–0.88) and cancer-specific survival (HR 0.78, 95% CI 0.64–0.94) in patients with prostate cancer compared with those not treated with metformin, although the incidence of prostate cancer was not associated with metformin [ 182 ]. Importantly, a dose-dependent inverse association between metformin and serum PSA levels was observed, which potentially affects the indication of prostate biopsy as well as detection of prostate cancer [ 216 ]. Metformin exerts its anti-cancer effect directly by acting on the tumor via inhibition of the mitochondrial electron transport chain and consequent activation of adenosine monophosphate-activated protein kinase, as well as indirectly by lowering systemic insulin levels [ 217 ].…”
Section: Chemoprevention Of Prostate Cancermentioning
confidence: 99%